Synthetic amorphous silica nanoparticles induce human endothelial cell inflammation and platelet aggregation : role of NF-kB and reactive nitrogen species - Corbalán-Penas, Juan José (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2010)
Background and purpose: The human population has been exposed to nanoparticles (particles with nano-dimensions) throughout all its evolutionary process; however, this exposure has been increased since the industrial revolution in the XIX century. Indeed, engineered nanoparticles are already used in many industries (e.g. computing engineering, aerospace) and in a wide range of applications, from cosmetics and food to paints and batteries. Therefore, humans are being increasingly more exposed to different types of nanoparticles. Furthermore, purposeful use of nanoparticles in humans is also growing as drug delivery systems and other nanomedical and nanopharmaceutical applications are being developed. Amorphous silica nanoparticles are one of the most frequently used group of engineered nanoparticles. However, interactions of these nanoparticles with human cells and tissues as well as their pharmacological and toxicological effects have not been elucidated yet. Inhalation is the main portal of entry of nanoparticles to the body and this is followed by translocation of particles to the vascular system and to possible interactions with endothelial cells and platelets. Therefore, the main objective of my PhD research was to investigate the pharmacological and toxicological effects of amorphous silica nanoparticles on platelet and endothelial cell function.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin